Associated factors with satisfaction of the first level of care in four peruvian health establishments - Valladares-Garrido, Mario J. (2020)
Objetive: Identify factors associated with satisfaction in the first level of care. Material and Methods: Cross-sectional study using the SERVQUAL survey to measure overall satisfaction and dimensions. Prevalence ratios (PR) were estimated using generalized linear models. Results: Of 120 respondents, 27.5% reported satisfaction. Female sex (RPa: 0.57, IC95%: 0.32-0.99), young (RPa: 0.33, IC95%: 0.19-0.60), adult (RPa: 0.33, IC95%: 0.19-0.60), older adult (RPa: 0.46, 95% CI: 0.28-0.76) and having SIS insurance (RPa: 0.68, 95% CI: 0.57-0.81) were negatively associated to satisfaction. Being treated in gynecology-obstetrics (RPa: 2.15, IC95%: 1.06-4.35), general medicine-specialties (RP: 1.58, IC95%: 1.38-1.81), and being a user (PR: 2.11, IC95%: 1.34-3.33) was positively associated with satisfaction. Conclusions: The satisfaction reported by users and / or companions in the first level of care is low. Female sex, belonging to three of four age groups and having SIS decreased the prevalence of perceived global satisfaction. While being cared for by gynecology-obstetrics, general medicine-specialties, being a user of care increased the level of overall satisfaction.